The Development of an Instructional Leadership Model for Outcome-Based Education at Private Higher Education Institutions in Cambodia - Hoeun, Chhourn Bun; Asavisanu, Poonpilas; Merritt , Matthew (Scholar: Human Sciences, 2021)
: The main purpose of this study is to develop an instructional leadership model for outcome-based education which has to be implemented in private higher education institutions in Cambodia. An exploratory sequential mixed-method (quantitative and qualitative) was employed for the study. Five private universities in Cambodia with 211 lecturers and 10 academic administrators participated in the study. Survey was used to collect the quantitative data with lecturers and interview was held to collect qualitative data with the academic administrators. For quantitative data, means, standard deviation and multiple regression were used to analyze the data and for qualitative data, content analysis was employed to analyze the data. The findings of instructional leadership and outcome-based education were consistent to the overall framework of the theories. Instructional leadership was found moderately practiced by the academic administrators of the five Cambodian private universities. The current practices of instructional leadership significantly correlated with the current outcome-based education practices. Four dimensions include Professional Development, Supervision of Curriculum Development and Instruction, and A Supportive and Collaborative Environment strongly and significantly correlated with all stages of outcome-based education. Three factors including Funding and Facilities, Cooperation, Culture, and Values, and Qualification, Skills, and Experience were found significantly affected instructional leadership practices. Outcome-based education was not found typically practiced by the selected universities though the quantitative data from survey gave greater mean score while the interviews offered in depth of the current practices. A model of instructional leadership for outcome-based education was developed with two parts: instructional leadership and outcome-based education. The new instructional leadership model is to be implemented by the students, lecturers, academic administrators, and higher education institutions in Cambodia.